Helping Mother Die - Triffletti, MD, Philip (North American Journal of Medicine and Science, 2010)
There are days you will always remember. December 5, 2009 my mother called and told me her friends commented she looked sick. She was jaundiced. I had just seen her on Thanksgiving and she seemed to be herself. She ate the Thanksgiving meal and appeared to have her usual appetite. She also had enjoyed one of our favorite family pastimes with her grandchildren, playing the card game whist. There was a cacophony of laughter coming from the dining room that night for hours as she masterfully played her high bids to victory. During November she was still doing all of her usual activities: line dancing and playing cards at the local senior centers, bowling, ballroom dancing, and singing in the church choir. That is why the phone call that night was somewhat surprising. She had been calling me in the past month with some non specific gastrointestinal complaints that she attributed to her metformin medication. After she consulted with her doctors, she was feeling improved without the medication during the past 2 weeks. Painless jaundice, though, made me very suspicious that she had a serious problem. My instincts would be proven correct.